Design of Solid State Tesla Coil With Music Playback Functionality - Naman Tanwar; M. Rajesh Kumar; Rani Chinnappa Naidu (IEEE Access, 2024)
This paper presents the design, simulation, and implementation of a solid state Tesla coil (SSTC) with music playback functionality through its arcs. It showcases various circuit designs that explore both feedback and non-feedback-based control mechanisms. The non-feedback based mechanism relies on an external oscillator circuit based on NE555 timer IC to drive the Tesla transformer coil at its resonance and the feedback based system relies on the selective amplification of a certain frequency at which the secondary coil is self-resonant. Additionally, to produce tones from the Tesla coil’s arcs, this paper implements a fixed gate signal interrupter circuit design that produces specific tones, as well as a music-based gate signal interrupter circuit design that produces music from the arcs. To verify the functionality of the design, the designed circuits were simulated in the LTspice SPICE simulation software and then implemented on a prototype board followed by a four-layer printed circuit board implementation. The primary coil of the Tesla transformer was controlled using an insulated-gate bipolar transistor (IGBT) based half bridge circuit.